2009
DOI: 10.1016/j.jvs.2009.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Gender and 30-day outcome in patients undergoing endovascular aneurysm repair (EVAR): An analysis using the ACS NSQIP dataset

Abstract: Mortality and morbidity were higher in women than men undergoing EVAR. Multivariate analysis showed that the increased risk of mortality was related to women presenting more emergently, more debilitated (recent weight loss and functional dependence), and requiring iliac or brachial exposure. After adjustment for multiple preoperative and operative factors, women remained at significantly higher risk for the development of a broad range of complications and increased length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 14 publications
9
91
1
Order By: Relevance
“…Similarly, Abedi et al 23. described higher mortality rates in women following elective EVAR (3·4 versus 2·1 per cent; P = 0·01), in addition to higher morbidity rates (17·8 versus 10·6 per cent; P < 0·001), which included a composite of 21 postoperative adverse events24.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, Abedi et al 23. described higher mortality rates in women following elective EVAR (3·4 versus 2·1 per cent; P = 0·01), in addition to higher morbidity rates (17·8 versus 10·6 per cent; P < 0·001), which included a composite of 21 postoperative adverse events24.…”
Section: Discussionmentioning
confidence: 82%
“…For instance, the US Medicare database shows that operative mortality after endovascular repair (now the majority procedure) is 3.2% in women compared with 1.8% in men, and similar findings have been reported in other studies. [90][91][92] Therefore, competing risks must be carefully considered before amending guidelines or recommendations for intervention in women.…”
Section: 87mentioning
confidence: 99%
“…At present, large aneurysms (over 5.5 cm in diameter) are referred to elective surgery (open surgery or endovascular aneurysm repair, EVAR), while optimal management of small aneurysms (less than 5.5 cm in diameter), which represents ca. 90 per cent of all screen-detected AAAs, 1 seems to be in favour of surveillance. Three trials showed that survival in patients with small AAAs is not significantly improved by elective surgery, 2-4 while other trials focused on whether early endovascular repair offer a survival benefit to patients with small AAAs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[3,4] Similarly, extremes of underweight have recently been described as a risk factor for surgery. [5][6][7] Several recent studies of critically and chronically ill patients, [8][9][10][11] and of patients undergoing certain procedures [12][13][14][15] suggest that overweight and obese patients may paradoxically have better outcomes than underweight patients, given an increased risk for death and catastrophic complications in the latter patients.…”
Section: Introductionmentioning
confidence: 99%